Neuromodulation of the Pineal Gland via Electrical Stimulation of Its Sympathetic Innervation Pathway - Lumsden, Susannah C.; Clarkson, Andrew N.; Cakmak, Yusuf Ozgur (Frontiers in Neuroscience, 2020)
Stimulation of the pineal gland via its sympathetic innervation pathway results in the production of N-acetylserotonin and melatonin. Melatonin has many therapeutic roles and is heavily implicated in the regulation of the sleep-wake cycle. In addition, N-acetylserotonin has recently been reported to promote neurogenesis in the brain. Upregulation of these indoleamines is possible via neuromodulation of the pineal gland. This is achieved by electrical stimulation of structures or fibres in the pineal gland sympathetic innervation pathway. Many studies have performed such pineal neuromodulation using both invasive and non-invasive methodologies. However, the effects of various experimental variables and stimulation paradigms have not yet been reviewed and evaluated. This review summarises these studies and presents the optimal experimental protocols and stimulation parameters necessary for maximal upregulation of melatonin metabolic output.